Germanic: Runes (Palaeohispanica. Revista sobre lenguas y culturas de la Hispania Antigua, 2020)
This paper offers a survey of the oldest runic inscriptions of the northern parts of Europe. Runic writing is attested from the second century onwards to the Middle Ages, and was in use in several parts of northern Europe during different periods. The language used is formulaic, making the impression that inscriptions in runes were for special occasions and not for daily use. Germanic society was a non-literate society until Christendom arrived and with it a literate culture. Runes are applied epigraphically; only in ecclesiastical contexts they are used in manuscripts, thus offering very useful secondary information about rune-names, for instance. Runes had names for mnemonical and symbolical purposes.